SWOT Analysis for Waste Management Recommendation of Bojong Village, Bogor Regency - Resti Ramadhanti; Andri N.R. Mardiah (Amcolabora, 2022)
Bogor Regency is a part of the National Central Activity System Jabodetabek Punjur, DKI Jakarta Province sub-urban. In the system, Bogor Regency plays the role of the nations capitals buffer zone as a residential/settlement area and as the upstream area in the watershed system so that water will flow from Bogor Regency to Jabodetabek area. This makes waste management is an important focus to be fixed because residences in Bogor Regency contributes emission at value 19.3 percent from all emission of Bogor Regency, is a largest waste producer in West Jawa, and the waste produced is not comparable with the management service. Because of the background, this research aims to formulate a waste management strategy for urban slum residence in Bogor Regency using SWOT and mapping analysis. The research concluded that Bojong Village needs to improve its disposal system by adding its waste infrastructure to shift villagers habit to burn trash and to pile up on the roadside, and then to cooperate with the centralized waste infrastructure of TPPAS Nambo and IPLT Cileungsi.